THE EFFECT DIGITAL CONTENT MARKETING AND PRODUCT QUALITY ON PURCHASING DECISIONS THROUGH BUYING INTEREST AS INTERVENING VARIABLE - Hilda Faradita Chasanah; Saino (Institute of Computer Science (IOCS), 2022)
Social media is a means of selecting and seeking information, including in the form of products and services needed. This is used by business people as a marketing opportunity in reading consumer behavior when searching, choosing, and considering a product online. This study aims to examine the effect of digital content marketing and the product quality on purchasing decisions for Scarlett products through buying interest as an intervening variable. The population of this research is the people of Surabaya, with a sampling technique using purposive sampling for 108 respondents. Processing data using path analysis technique with SmartPLS version 3.3.9. The results of this study are that there is a direct influence of digital content marketing on buying interest, product quality on buying interest, product quality on purchasing decisions, and buying interest on purchasing decisions stated to have a positive and significant effect. The direct influence of digital content marketing on purchasing decisions has no effect. In addition, the indirect effect of digital content marketing on purchasing decisions through buying interest as an intervening mediation variable shows no effect. The influence of product quality on purchasing decisions through buying interest as an intervening mediation variable has a positive and significant influence partially (partial mediation).